2023
DOI: 10.3390/su15064911
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Farmers’ Adaptation Strategies to Climate Change and Sustainable Development Goals in Tanzania, East Africa

Abstract: This study investigated the potential adaptation measures for farmers in the Mwanga and Same Districts of Tanzania and then assessed their positive and negative interactions towards potential contributions to the selected sustainable development goal (SDG) indicators of no poverty and zero hunger. A total of 200 household surveys were conducted, and 36 participants were interviewed as key informants. Moreover, four focus group discussions were conducted to identify potential adaptation strategies in the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Directly or indirectly, they will have an influence on national, regional, as well as the global development agenda. Similar studies that focused on the agricultural sector also observed that climate change response strategies can significantly contribute towards attainment of SDGs, for example, Magesa et al (2023) observed positive implications of farmers' adaptation strategies to SDGs 1 and 2 in Tanzania. Implications of climate change response strategies on SDGs can be observed within the water sector in the Mutirikwi sub-catchment.…”
Section: Discussionmentioning
confidence: 52%
“…Directly or indirectly, they will have an influence on national, regional, as well as the global development agenda. Similar studies that focused on the agricultural sector also observed that climate change response strategies can significantly contribute towards attainment of SDGs, for example, Magesa et al (2023) observed positive implications of farmers' adaptation strategies to SDGs 1 and 2 in Tanzania. Implications of climate change response strategies on SDGs can be observed within the water sector in the Mutirikwi sub-catchment.…”
Section: Discussionmentioning
confidence: 52%
“…These agroecological practices replicate the local environment, are affordable, ecologically friendly, and culturally aligned, making them particularly beneficial for smallholder farmers in poor and middle-income countries facing the climate crisis, helping them to build climateresilient communities that address the interrelated issues of climate change, food security, and human health. While these adaptation strategies can reduce the impact of climate change on agricultural productivity, at the same time, other studies, such as [87], suggest that concrete irrigation water supply, extension, transfer of knowledge, technologies, and credit facilities must also be used for better yields and positive impacts. Strategic planning, implementation, and monitoring of cropping systems according to the changing climate plays a pivotal role in sustainable food production.…”
Section: Adapting To Changing Climatementioning
confidence: 99%
“…A diversity of concepts, and a wide spectrum of SD goals, have been the subjects of scientific research [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. An additional area of scientific research is the implementation of sustainable development goals by individual countries [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Definitions and Aim Of Sustainabilitymentioning
confidence: 99%